Analysis of the Effect of Compensation and Intellectual Capital Through Job Satisfaction on Performance - M. Yusuf Alfian Rendra Anggoro KR; A. Nur Fitrianti; Sherry Adelia Natsir Kalla (International Journal of Scientific Multidisciplinary Research, 2023)
This study aims: (1)to examine and analyze the effect of compensation and intellectual capital on job satisfaction, (2)to examine and analyze the effect of compensation and intellectual capital on employee performance, (3)to examine and analyze the effect of job satisfaction on employee performance, and (4)to examine and analyze the effect of compensation and intellectual capital on employee performance through job satisfaction.This study uses primary data through a survey of 335 employees as a sample of a total of 2.076 employees. Data were analyzed using the structural equation modeling (SEM) program.The results showed: (1)compensation and intellectual capital have a positive and significant effect on job satisfaction, (2)compensation and intellectual capital have a positive and significant effect on employee performance, (3)job satisfaction has a positive and significant effect on employee performance, and (4)compensation and intellectual capital have a positive and significant effect on employee performance through job satisfaction